Cameral opening as a surgical maneuver in patients with diabetes mellitus 1 in pediatric dentistry: odontologia pediatrica - Farias-Vera, Javier (2025)
The access or chamber opening is the first surgical maneuver performed in the endodontic technique, so the final result of the root canal treatment will depend on it. The chamber opening is not an emergency treatment, but a dental procedure that is part of the endodontic treatment. It consists of a surgical maneuver aimed at eliminating the pulp chamber of a tooth in order to access the root canals, and is performed by an endodontic specialist. In this report we present the case of a 14-year-old adolescent girl with a history of Type 1 Diabetes Mellitus (DM1), diagnosed four years ago, who came for consultation due to persistent odontalgia and tooth sensitivity with a two-month evolution. We describe the clinical findings, the preoperative evaluation and the root canal opening procedure performed with the aim of relieving the pain and improving the patient's oral health.